ANALISIS PERILAKU MASYARAKAT TERHADAP KEJADIAN PENYAKIT DEGENERATIF DI WILAYAH KERJA PUSKESMAS KOTA BANJARMASIN - Achmad Rizal; Agus Jalpi (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2022)
Degenerative disease is a contributor to death from non-communicable diseases (NCD) in the last 10years which has increased from 41.7%. The latest survey in Indonesia shows PTM dominates the top 10 causes ofdeath in all age groups, with stroke, which is a complication as the number one cause of death. This studyaims to determine the relationship between length of smoking and coffee drinking habits with the incidenceof hypertension in the working area of the Banjarmasin City Health Center which was carried out in 2019.This type of research is an analytical survey with a cross-sectional research design. The subjects in this studyamounted to 57 respondents, consisting of male active smokers and consuming coffee. Data were obtainedthrough questionnaires and direct interviews as well as physical examination in the form of blood pressuremeasurements by puskesmas officers, which were then analyzed by chi-square test (α=0.05). The results ofthe statistical test showed that there was a relationship between length of smoking and the incidence ofhypertension (P=0.000), and the habit of drinking coffee with the incidence of hypertension (P=0.002).Suggestions that can be given in research are for puskesmas to further increase public knowledge abouthealth through counseling, especially about the incidence of hypertension, for health workers to optimizecounseling about the incidence of hypertension, especially for men who smoke and consume coffee.experience and add insight, and for other researchers can be used as basic data for further research.